Online Learning During the Covid-19 Pandemic from the Perspective of Parsons’ Structural Functional Theory - Ellya Rohati; Isa Anshori; Mufarrihul Hazin (STAI Ma'had Aly Al-Hikam Malang, 2021)
The Covid-19 pandemic results social changes significantly in the world of education, from offline learning to online learning. In order not to experience cultural lag, this article offers a functional structural theory initiated by Talcott Parsons to examine the implementation of online learning, through the AGIL (Adaptation, Goal Attainment, Integration, Latency) scheme. This article recommends to all involved and interested parties to immediately adapt to online learning, so that the online learning can meet the educational and learning objectives that have been proclaimed. Therefore, integration between three educational centres is needed, such as school, families and communities; so that education as a cultural pattern inherent in Indonesian society is maintained even during the Covid-19 pandemic. More than that, the implementation of online learning must maintain a new cultural pattern during the Covid-19 pandemic, namely complying with health protocol standards.